Family-building decision aid and planning tool for young adult women after cancer treatment: protocol for preliminary testing of a web-based decision support intervention in a single-arm pilot study. Issue 12 (29th December 2019) - Benedict, Catherine; Ford, Jennifer S; Schapira, Lidia; Simon, Pamela; Spiegel, David; Diefenbach, Michael
Abstract : Introduction: Many young adult female (YA-F) cancer survivors who received gonadotoxic therapy will experience fertility problems. After cancer, having a child will often require assisted reproductive technology (ART), surrogacy or adoption. However, there are significant informational, psychosocial, financial and logistical barriers to pursuing these options. Survivors report high rates of decision uncertainty and distress related to family-building decisions. The aim of this study is to pilot test a web-based decision aid and planning tool for family-building after cancer. Methods and analysis: The pilot study will use a single-arm trial design to test the feasibility and acceptability (aim 1) and obtain effect size estimates of the decision support intervention (aim 2). The target sample size is 100. Participants will include YA-F survivors (aged 18–45 years) who are post-treatment and have not completed desired family-building. A longitudinal prepost design will be conducted. Participants will complete three psychosocial assessment surveys over a 3-month time period to track decisional conflict (primary outcome) and cognitive, emotional, and behavioural functioning (secondary outcomes). After completing the baseline survey (T1; pre-intervention), participants will have access to the decision aid website. Postintervention surveys will be administered at 1-month (T2) and 3-month (T3) follow-up time points. Feasibility and acceptability metrics will be analysed. Pairwise t-tests will test mean scores of outcome variables from T1 to T2. Effect size estimates (Cohen's d) will be calculated. Google analytics will evaluate user engagement with the website over the study period. Baseline and follow-up data will examine measures of feasibility, acceptability and intervention effect size. Ethics and dissemination: This will be the first test of a supportive intervention to guide YA-F cancer survivors in family-building decisions and early planning. Study findings will inform intervention development. Future directions will include a randomised controlled trial to test intervention efficacy over a longer time period. Trial registration number: NCT04059237 ; Pre-results.